(untitled) (MAUSAM, 1979)
The, agro meteorological aspects of moisture availability for the seeding zone are detailed. A methodology for delineating, from weekly rainfall and number of rainy days, sowable periods is presented. The climatological picture obtained, for the period 1941-65, at representative stations in Karnataka is used to outline the sowing strategy in the different regions.